USING INFORMATION TECHNOLOGY IN FUNDRAISING FOR SOCIAL PROJECTS AND STARTUPS - Kobushko, Ihor; Kotenko, Nataliia; Boiko, Kateryna (Social Economics, 2018)
The article identifies online fundraising as a process of resources attracting using mobile and Internet technologies to build and strengthen interaction between stakeholders interested in the success of a social project or startup. The authors compare online fundraising with traditional methods of attracting funds according to such administrative and financial criteria as the possibility of attracting supporters of the idea; level of trust in organization and project; real "visibility" of the organization; geographical constraints; efficiency of administrative expenses; average speed of feedback (result) receipt; average contribution amount; managing donor databases; portrait of the donor. The key tools of online fundraising are highlighted. Based on the ethical principle of anonymity of fundraising activity and comparison of subjective and external assessments of motivational factors of fundraising, application of blockchain technologies and related monetary institutions are proposed to finance social projects and startups as they serve as anonymous online payments and offset some shortcomings of electronic payment systems. It is proved that such commonly known disadvantages of cryptocurrencies as hyper-volatility, uncertainty of legal status, insecurity from hacker attacks on electronic crypt-purses, the need to remove excess profits and taxes from the shadow, the absence of the possibility to stop or cancel payments turn into indirect advantages for social projects and startups, which become more competitive compared to ordinary direct or financial investments. At the same time, the authors emphasize the increased risks and responsibilities for social project and startups managers when applying crypto-currency and ICO (Initial Coins Offering) and the issue of the sustainability of e-financing in globalizing and digitizing economies.